Exploring the Use of AR in Teaching Grammar to ESL Students: A Mixed-Methods Study - Eva König; Marieke de Boer; Khadija Gnama (International Journal of Language and Ubiquitous Learning, 2025)
Background. The rapid advancement of educational technology has opened new possibilities for integrating Augmented Reality (AR) into English language teaching, particularly in grammar instruction for ESL learners. Traditional grammar teaching often depends on abstract explanations and repetitive drills, which can reduce learner engagement and limit contextual understanding. Purpose. This study aimed to examine the effectiveness of AR-based instruction in improving ESL students’ grammatical competence and learning engagement compared to conventional grammar teaching methods. It also sought to explore learners’ perceptions of AR as a tool for understanding abstract grammatical concepts. Method. A mixed-method research design was employed involving 80 intermediate-level ESL learners divided into an experimental group receiving AR-based grammar instruction and a control group receiving traditional instruction. Quantitative data were collected through pre- and post-tests. Results. The findings revealed a significant improvement in the experimental group’s post-test grammar scores compared to the control group (p < 0.01), indicating that AR-based instruction positively influenced grammatical mastery. Qualitative results showed that learners perceived AR as highly engaging, motivating, and effective in helping them visualize and understand abstract grammatical concepts. Conclusion. By transforming abstract language forms into immersive and context-rich learning experiences, AR promotes deeper understanding, learner autonomy, and sustained motivation, demonstrating strong potential to redefine grammar teaching through student-centered and technology-enhanced approaches.